Strategic Priority Of Students’ Online Buying Behaviour In The Pandemic Era - Jozef R. Raco; Yulius Raton; James V. Krejci; Johannes A. Timbuleng; Ronaldo Rottie (Jurnal Manajemen, 2023)
Online buying is growing and has become very common during the COVID-19 pandemic period. A large number of companies take advantage of this method, and many consumers find it helpful to the existing technology. In this study, the researcher wanted to investigate the strategic priority of convenience for online Shopping of the Generation Y consumer. Data were collected from college students and analysed using Analytical Hierarchy Process (AHP). The results of the analysis showed that the criteria of easy comparison of prices of the goods to be purchased are the highest value (28.544 per cent). The global weight calculation showed that the availability of information in the form of text and images is the highest (13.789 per cent). Sensitivity analysis showed that the results of this global weight are very sensitive to a change in the criteria. This study provides benefits by focusing online businesses' attention on the appearance of their application features, both text, images, and graphics. Competitive product prices must also be a concern for online businesses.